The Last Peasants, Temptation - Macqueen, Angus (October Films, 2003)
Verzio FF The Oprisc family have dominated the village for generations, through World Wars, occupation and communism. But ten years of "capitalism and democracy" is threatening everything they stand for. They own the water-driven threshing machine and take 10% of the villages corn. But their children do not want to take over the farm. The film tells the story of the collapse of a crumbling world, undermined by the dream of a little known and barely understood world outside.